2020
DOI: 10.1128/msystems.00731-19
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Metagenome-Derived Metrics Verify and Delineate Bacterial Species Boundaries

Abstract: Longstanding questions relate to the existence of naturally distinct bacterial species and genetic approaches to distinguish them. Bacterial genomes in public databases form distinct groups, but these databases are subject to isolation and deposition biases. To avoid these biases, we compared 5,203 bacterial genomes from 1,457 environmental metagenomic samples to test for distinct clouds of diversity and evaluated metrics that could be used to define the species boundary. Bacterial genomes from the human gut, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
169
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 54 publications
4
169
1
Order By: Relevance
“…Despite extensive horizontal gene transfer in bacteria [ 3 ], recent studies have shown that bacteria exist as discrete populations, which can be identified based on metagenomic read recruitment [ 25 , 26 , 27 , 28 ] or gANI (genomic average nucleotide identity) [ 11 , 29 , 30 ]. Bacteria belonging to the same population generally have more than 95% gANI with each other, whereas bacteria from different populations typically have less than 90% gANI [ 11 , 30 ]. These populations have therefore also been referred to as “sequence-discrete populations” (SDPs) or even “species” [ 11 , 27 , 30 ], although the latter term continues to be controversial for bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite extensive horizontal gene transfer in bacteria [ 3 ], recent studies have shown that bacteria exist as discrete populations, which can be identified based on metagenomic read recruitment [ 25 , 26 , 27 , 28 ] or gANI (genomic average nucleotide identity) [ 11 , 29 , 30 ]. Bacteria belonging to the same population generally have more than 95% gANI with each other, whereas bacteria from different populations typically have less than 90% gANI [ 11 , 30 ]. These populations have therefore also been referred to as “sequence-discrete populations” (SDPs) or even “species” [ 11 , 27 , 30 ], although the latter term continues to be controversial for bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria belonging to the same population generally have more than 95% gANI with each other, whereas bacteria from different populations typically have less than 90% gANI [ 11 , 30 ]. These populations have therefore also been referred to as “sequence-discrete populations” (SDPs) or even “species” [ 11 , 27 , 30 ], although the latter term continues to be controversial for bacteria. For the western honeybee, Apis mellifera , a recent metagenomic study identified 1–4 SDPs per 16S rRNA phylotype in the gut microbiota [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we do not attribute this observed genome similarity to index hopping during sequencing (see Supplementary Note 2). Even at the species level (>95% ANI 39 ), most pairs of analyzed sites share no more than one species in common (SI Fig 3). The overall lack of similarity between these ten groundwater sites--at the phylum level, species level, and strain level-indicates a high degree of specialization based on local hydrogeochemical conditions.…”
Section: Groundwater Communities Are Highly Distinct and Vary Dramatimentioning
confidence: 99%
“…Collection, and rumen-specific MAGs Recent analyses support a 95% ANI threshold to delineate microbial species 51,52 . The ANI values of MAGs from the current study and genomes from the GTDB (a curated and dereplicated collection of 22,441 genomes in the GTDB-Tk FastANI database 21 ), Hungate1000 project 3 , and Stewart et al 4,5 were compared in a pairwise fashion with FastANI (version 1.1) 51 .…”
Section: Similarity Of Reconstructed Mags To Gtdb Reference Genomes mentioning
confidence: 99%